(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This paper explores the profound influence of artificial intelligence, specifically ChatGPT, on the English lexicon through the introduction of neologisms, semantic shifts, metaphorical extensions, and discourse-level transformations. As AI-powered conversational agents enter mainstream usage, their linguistic output and the cultural environment they help create foster the emergence of new lexical items and novel usages of existing words. Drawing upon corpus linguistics, semantic field theory, and discourse analysis, the study identifies key lexical innovations associated with ChatGPT and explores their integration into academic, media, and informal communication. The findings shed light on how technology is not only shaping language use but also influencing the conceptual frameworks through which we interpret communication, knowledge, and human-machine interaction.